Optimizing Saudi bank stock performance through response surface methodology approach - Al-Otaibi, Mohammed Ibrahim; Mohd Nor, Normaziah; Yusri, Yusniyati (Asian Scholars Network, 2024)
One of the most effective methods for developing countries to increase their revenue is through the implementation of value-added tax (VAT). Nevertheless, market capitalization (MC) and trading volume (TV) are potent indicators of stock performance (SP). The objective of this paper is to determine the optimum VAT, TV, and MC on SP of Alinma Bank (ANB) and Samba Financial Group (SFG) company in Saudi Arabia, for the first time. The event study method was implemented to determine the abnormal return for each event within a specific timeframe of 15 days. Response Surface Methodology (RSM) was employed to optimize the results. On the 4th day prior to the 5% applied VAT, the model predicted an optimal result for ANB company with 2.98% abnormal return, with a 0% VAT, 37.70% TV, and a 3.16% MC. In contrast, the model anticipated an optimal outcome for the SFG company with 2.55% abnormal return at 5% VAT, 168.93% TV and 9.85% MC on the 4th day prior to the 15% VAT raise. Additionally, this research determined that there is a correlation between the variables, which VAT has a higher impact than MC and TV on SP.